Expert System Diagnose Eye Diseases Using Case-Based Reasoning Method with Jaccard 3W Algorithm - Sait, M Ibnu; Putri, Raissa Amanda (International Journal Software Engineering and Computer Science (IJSECS), 2023)
The Case Based Reasoning method is a method that applies 4 stages of the process, namely Retrieve, Reuse, Revise, and Retain. The workings of the system in general are guided by the knowledge base possessed by the system which originates from cases that have been handled by an expert. Then the level of similarity is calculated with the new cases entered by the user using the 3W Jaccard Algorithm, based on the level of similarity of these cases, the system will issue the conclusions drawn. This research resulted in an expert system application to detect eye disease. The method used in calculating the Case Based Reasoning (CBR) method with the 3W Jaccard Algorithm. This application diagnosis types of eye disease based on the results of the largest percentage and can provide a solution to the eye disease you are experiencing.